2004
DOI: 10.1149/1.1704611
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Al-Mo Alloys from the Lewis Acidic Aluminum Chloride-1-ethyl-3-methylimidazolium Chloride Molten Salt

Abstract: The electrodeposition of aluminum-molybdenum alloys was examined at copper rotating disk and wire substrates in the Lewis acidic 66.7-33.3 mol % aluminum chloride-1-ethyl-3-methylimidazolium chloride molten salt containing Mo͑II͒ in the form of dissolved (Mo 6 Cl 8 )Cl 4 . The molybdenum content of the electrodeposits depended on the electrode rotation rate, Mo͑II͒ concentration, and bath temperature. It was possible to produce nonequilibrium alloys containing up to 11 atom % Mo. These alloy deposits were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 40 publications
6
65
0
1
Order By: Relevance
“…These alloys are formed at or less than 0 V vs. Al(III)/Al without difficulty. Many Al alloy systems have been prepared by this route, including Al-Mg, 77 Al-Ti, [78][79][80] Al-Zr, 81 AlHf, 72 Al-V, 82 Al-Cr, [83][84][85][86][87][88] Al-Mo, 89 Al-W, 73 Al-Mn, 90,91 Al-In, 74 and Al-La. 44 It has been determined by X-ray diffraction techniques that Al-Zr, Al-Cr, Al-Mo, Al-W and Al-Mn in particular form amorphous glass phases.…”
Section: Electrodeposition Aluminum Alloys From Haloaluminate Rtilsmentioning
confidence: 99%
“…These alloys are formed at or less than 0 V vs. Al(III)/Al without difficulty. Many Al alloy systems have been prepared by this route, including Al-Mg, 77 Al-Ti, [78][79][80] Al-Zr, 81 AlHf, 72 Al-V, 82 Al-Cr, [83][84][85][86][87][88] Al-Mo, 89 Al-W, 73 Al-Mn, 90,91 Al-In, 74 and Al-La. 44 It has been determined by X-ray diffraction techniques that Al-Zr, Al-Cr, Al-Mo, Al-W and Al-Mn in particular form amorphous glass phases.…”
Section: Electrodeposition Aluminum Alloys From Haloaluminate Rtilsmentioning
confidence: 99%
“…A representative ionic liquid used for the electrodeposition of Al alloys is Lewis acidic 1-ethyl-3-methylimidazolium chloride (EMIC)-AlCl 3 (where the AlCl 3 /EMIC molar ratio >1). Reports on the electrodeposition of Al alloys including Al-Ni, 13 Al-Ti, 14 Al-V, 15 Al-Zr, 16 Al-Mo, 17 Al-Mn, 18 and Al-Hf 19 are available in the literature. A previous study revealed that electrodeposition in a EMIC-AlCl 3 bath with the addition of W(IV) chloride (WCl 4 ) yielded Al-W alloys, but the W content was lower than 1 at.%.…”
mentioning
confidence: 99%
“…Of the electrodeposited alloys in this list, amorphous Al-Mo alloys show the best resistance to chloride-induced pitting corrosion (ca. +0.8 V vs. pure Al) [5]. However, we found that the addition of a relatively small amount of a second transition element, notably Mn, significantly improves the corrosion resistance of the Al-Mo alloy system [6].…”
Section: Introductionmentioning
confidence: 66%
“…[10]. As discussed in the article, in the pure melt, a stripping wave for electrodeposited Al initiates at around 0 V, but this wave is replaced by waves corresponding to the stripping of the electrodeposited Al-Mo or Al-Ti alloys in those solutions containing Mo(II) or Ti(II), respectively [5,11]. Cyclic staircase voltammograms recorded in the 66.7 m/o RTIL containing both Mo(II) and Ti(II), regardless of the Mo(II)/Ti(II) concentration ratio, C Mo(II) /C Ti(II) , are more or less similar in appearance to that recorded in the Mo(II) solution.…”
Section: Characterization Of the Electrodepositsmentioning
confidence: 97%